Energy Consumption, ICTs Development and Environmental Quality among ECOWAS: Array - Akanbi, Bosede; Akintunde, Temitope (Acta Universitatis Danubius. Œconomica, 2021)
Relationships among energy consumption, environmental issues and other macroeconomic variables provide an extensive literature for a large number of studies across the world. Existing studies have explored the nature and direction of the linkage between energy consumption, income, electricity price, inflation, exchange rate and trade openness. However, relationship among ICT development, energy consumption and environmental quality has received little attention particularly among Economic Community of West African States. This study investigated the dynamic linkages among energy consumption, ICT development and environmental quality using the panel of 6 countries in West Africa using data from U.S. Energy Information Administration (EIA) and World Development Indicators and using Generalized Method of Moments (GMM). It was found that carbon dioxide emissions increased energy consumption. Also, mobile telephone subscription had negative but insignificant relationship with environmental quality and fixed line subscription has significant negative impact on environmental quality within the period under study. In addition, environmental damage increased as economies of these selected countries grew, hence, there is no inverted U-shape relationship found between economic growth and environmental quality. The results obviously would facilitate the policy planners to formulate related policies in line with carbon free economy thereby enhancing sustainable development in selected countries.